2012
DOI: 10.1186/1471-2407-12-52
|View full text |Cite
|
Sign up to set email alerts
|

Proteins and carbohydrates in nipple aspirate fluid predict the presence of atypia and cancer in women requiring diagnostic breast biopsy

Abstract: BackgroundHerein we present the results of two related investigations. The first study determined if concentrations in breast nipple discharge (ND) of two proteins (urinary plasminogen activator, uPA and its inhibitor, PAI-1) predicted the presence of breast atypia and cancer in pre- and/or postmenopausal women requiring surgery because of a suspicious breast lesion. The second study assessed if these proteins increased the predictive ability of a carbohydrate (Thomsen Friedenreich, TF) which we previously dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Noninvasive biofluids are easily-accessibe biological samples, which usually do not involve instrument insertion into the patient’s body. Besides breath, urine, saliva and sweat, other minimally invasive procedures such as nipple aspiration along with ductal lavage can provide many cells collected from the milk ducts [32]. …”
Section: Array-based Cancer Diagnosticsmentioning
confidence: 99%
“…Noninvasive biofluids are easily-accessibe biological samples, which usually do not involve instrument insertion into the patient’s body. Besides breath, urine, saliva and sweat, other minimally invasive procedures such as nipple aspiration along with ductal lavage can provide many cells collected from the milk ducts [32]. …”
Section: Array-based Cancer Diagnosticsmentioning
confidence: 99%
“…However, the combination of both TF and uPA biomarkers in nipple aspirate fluid predicted breast cancer in both pre- and postmenopausal women with 84-92% accuracy 21. When used in combination with uPA, PAI-1 and TF have higher predictive capacities to detect breast cancer and achieved accuracy values of 97-100% 21 in nipple aspirate fluid. Therefore, large clinical trials are needed to validate the combination of these biomarkers for the early diagnosis of breast cancer.…”
Section: Potential Biomarkers For the Diagnosis And Prognosis Of Breamentioning
confidence: 99%
“…In the frame of searching cancer biomarkers in breast microenvironment [26,27], a recent study published in BMC Cancer [65] reports an interesting and innovative combinatory analysis of three well-known predictive biomarkers (uPA, PAI-1, and TF) in NAF collected noninvasively (or spontaneously secreted) from healthy women, patients with breast atypia and cancer (in pre- and post-menopause), requiring surgery because of a suspicious breast lesions.…”
Section: Reviewmentioning
confidence: 99%
“…Although these biomolecules appeared individually not perfectly accurate in predicting the presence of BC during different menopausal status, Sauter’s research team demonstrated the innovative biomarker combination in NAF [65]: 1) uPA concentration alone was more predictive of disease in premenopausal women (AUC values 0.83-0.87); 2) the range of AUC values for uPA+PAI-1 expression in all women was 0.72-0.75; 3) TF antigen alone was better at predicting BC in postmenopausal women showing range of AUC values 0.81-0.83. While TF antigen + uPA expression predicted breast diseases in both pre- and post-menopausal women with 84-92% of accuracy, interestingly and surprisingly when TF uPA + PAI-1 were combined, the predictive ability approached 97-100% allowing the near absolute prediction of both atypia or cancer disease in women requiring surgery because of a suspicious breast lesions (Figure  1).…”
Section: Reviewmentioning
confidence: 99%